Comparative analysis of NTRUEncrypt modified post-quantum cryptographic system and standard RSA cryptosystem - P. V. Razumov; I. A. Smirnov; I. A. Pilipenko; A. V. Selyova; L. V. Cherkesova (Advanced Engineering Research)
Introduction. The NTRUEncrypt cryptographic system, the calculation of the algorithmic complexity of the development of the NTRUEncrypt cryptosystem and its modifications are considered. The study objectives are to develop NTRUEncrypt, an efficient post-quantum cryptographic algorithm, which has high cryptographic resistance to quantum computer attacks, to work out a modification of the proposed algorithm, to analyze and experimentally validate its advantages.Materials and Methods. A description of the NTRUEncrypt encryption system is proposed. The modification of the considered algorithm is studied; the block diagram of the implementation of the software based on it is presented. An example of the software operation and its characteristic is given. The reliability of the results is proved using the Mann-Whitney U test. During the experiment, the third-party software implementation of the RSA cryptosystem was used. A Stopwatch class element was introduced in the source code of all three programs of NTRUEncrypt, RSA, and NTRUEncrypt modifications. This class provides a set of methods and properties that can be used for the precise measurement of the execution time. Thus, it became possible to record the results of the time spent on all three basic stages: key creation, encryption and decryption of the message.Research Results. The advantages of the developed cryptosystems in terms of the performance characteristics are proved. An experimental comparison of the implemented NTRUEncrypt algorithm and its modification is performed. All advantages of the latter are indicated.Discussion and Conclusions. The advantage of using the NTRUEncrypt algorithm modification is experimentally validated. The new application is 25% faster to perform general work on key generation, encryption and decryption. In addition, the internal memory usage is optimized through reducing the weight of the source program file and the size of the secret key. When attempting to crack a ciphertext, cryptographic robustness and complexity of using quantum algorithms are shown.